Evaluation of Novel Imidazotetrazine Analogues Designed to Overcome Temozolomide Resistance and Glioblastoma Regrowth - Ramirez, Yulian P.; Mladek, Ann C.; Phillips, Roger M.; Gynther, Mikko; Rautio, Jarkko; Ross, Alonzo H.; Wheelhouse, Richard T.; Sakaria, Jann N. (Molecular cancer therapeutics, 2015)
The cellular responses to two new temozolomide (TMZ) analogues, DP68 and DP86, acting against glioblastoma multiforme (GBM) cell lines and primary culture models are reported. Dose–response analysis of cultured GBM cells revealed that DP68 is more potent than DP86 and TMZ and that DP68 was effective even in cell lines resistant to TMZ. On the basis of a serial neurosphere assay, DP68 inhibits repopulation of these cultures at low concentrations. The efficacy of these compounds was independent of MGMT and MMR functions. DP68-induced interstrand DNA cross-links were demonstrated with H2O2-treated cells. Furthermore, DP68 induced a distinct cell–cycle arrest with accumulation of cells in S phase that is not observed for TMZ. Consistent with this biologic response, DP68 induces a strong DNA damage response, including phosphorylation of ATM, Chk1 and Chk2 kinases, KAP1, and histone variant H2AX. Suppression of FANCD2 expression or ATR expression/kinase activity enhanced antiglioblastoma effects of DP68. Initial pharmacokinetic analysis revealed rapid elimination of these drugs from serum. Collectively, these data demonstrate that DP68 is a novel and potent antiglioblastoma compound that circumvents TMZ resistance, likely as a result of its independence from MGMT and mismatch repair and its capacity to cross-link strands of DNA. Mol Cancer Ther; 14(1); 111–9. ©2014 AACR.